Traduction du futur antérieur de probabilité en polonais - Ciszewska, Ewa (Neophilologica, 2007)
The future tense futur antérieur, in addition to other values, mainly temporary ones, may indicate probability. The article presents the result of the analysis of the Polish equivalents of this future tense. The analysis is based on the corpus of literary texts of 19th and 20th centuries translated into Polish. The futur antérieur is generally translated through the construction with the verb musieć, various opinion verbs and modal adverbs which indicate the degree of certainty of the speaker towards the contents of his utterance. The absence of the modal expression is possible only in interrogative clauses, in alternatives, with indefinite pronouns or when preceding verb indicates the probability.